Grammatical Error Analysis of Postgraduate Theses in Natural Sciences - Fiaz, Arifa; Rubab, Iram (Pakistan Languages and Humanities Review, 2024)
This aim of the study is to identify the grammatical errors made by Natural Sciences Postgraduate students in their theses which were classified in terms of ‘surface taxonomy’ introduced by Ellis & Barkhuizen (2005) i.e, ‘omission’, ‘addition’, ‘misformation’ and ‘misordering’. In this regard, data was collected from the University library in relation to Departments of Zoology, Botany, Physics and Chemistry. Four theses from each department were selected and total sample was comprised of sixteen theses. And then data was qualitatively analyzed. Findings revealed that mostly errors were observed in ‘omission’ category, which were 50.25% collectively and least errors were regarding ‘misordering’. Whereas, the ‘misformation’ category contains 34.55% errors and ‘addition’ category contains 14.02% errors. It shows the students don’t have sufficient competency in English grammar to present their thoughts in their theses. This study will be beneficial for the stakeholders. ESP writing courses, workshops and trainings are suggested to improve their writing skills.